Identical Twins? : Destination-Based Cash-Flow Taxes Versus Consumption Taxes with Payroll Subsidies - Carton, Benjamin (IMF Working Papers; Working Paper ;, 2017)
The Global Integrated Monetary and Fiscal model (GIMF) is a multi-region, forward-looking, DSGE model developed by the Economic Modeling Division of the IMF for policy analysis and international economic research. This paper uses GIMF to illustrate when a destination-based cash-flow tax is equivalent to a combination of a consumption tax and a labor subsidy, as the latter combination have been advocated as proxies for the implementation of destination-based cash-flow taxes. The paper documents the conditions under which both types of taxes are identical and how the equivalence in terms of the real economy and tax revenue responses can be broken, namely after the introduction of finitely lived consumers that value government debt as net wealth (real economy) and the introduction of untaxed government expenditure (tax revenue).